STUDI PENERAPAN TEKNOLOGI TEPAT GUNA TERHADAP PERUBAHAN SOSIAL NELAYAN KARAMBA DI KELURAHAN PEMBUANG HULU I, KECAMATAN HANAU, KABUPATEN SERUYAN, PROVINSI KALIMANTAN TENGAH - Yos Andy Tangkasiang; Akhmad Syarif (FISIPOL Universitas PGRI Palangka Raya, 2022)
Although opportunities for transfer and mastery of various technologies are very possible, it does not mean that all technologies developed in Indonesia can have a positive influence, but can also have a negative effect. Every technology that is transferred and developed must be adjusted to cultural preferences, social circumstances, and other environmental conditions. As in the area of Pembuang Hulu I Subdistrict, Hanau Subdistrict, Seruyan Regency, Central Kalimantan Province, karamba technology has been widely known by its people, and the appropriate technology applied is a sharpening of the technology that has been used by local communities. As a result of the implementation of this technology, there have been social changes experienced by the population consciously or unconsciously, resulting in a consumptive lifestyle due to an increase in income.